ISOLASI BAKTERI SELULOLITIK DAN KARAKTERISASI ENZIMNYA - Meryandini, Anja; Widosari, Wahyu; Maranatha, Besty; Sunarti, Titi Candra; Rachmania, Nisa; Satria, Hasrul (Makara Journal of Science, 2009)
Isolation of Cellulolytic Bacteria and Characterization of the Enzyme. Four of cellulolitic bacteria isolates had been characterized. The determination of cellulase activity was conducted at the highest production time, using crude enzymes with the modification of Miller methods (1959) on pure cellulose substrates such as CMC (Carboxymethyl cellulose), Avicel and Filter paper Whatman No. 1 as well as agriculture waste such as rice straw, corn cob and banana peel. Cellulase from C4-4, C5-1, C5-3 and C11-1 showed optimum activity at pH 5, 70°C, pH 3.5, 90°C, pH 5, 80°C and pH 8, 70°C, respectively. Avicel is a appropriate substrate for C4-4 cellulase whereas CMC for the other three. C11-1 cellulase has the highest cellulase enzyme activity on rice straw substrate whereas C4-4 cellulase on banana peel substrates. C5-1 and C5-3 cellulase have relatively low cellulase activities in degrading substrates of agriculture waste. However, isolates of C5-1 and C5-3 have high cellulase activities on banana peel substrates.